SYNTHESIS OF TERPINEOL FROM α-PINENE CATALYZED BY TCA/Y-ZEOLITE - Nanik Wijayati; Harno Dwi Pranowo; Jumina Jumina; Triyono Triyono (Indonesian Journal of Chemistry, 2011)
The hydration of a-pinene has been studied in the presence of TCA/Y-Zeolite catalyse. The catalyst was prepared by impregnating trichloroacetic acid (TCA) on support of Y-Zeolite. The TCA/Y-Zeolite catalyst converted a-pinene into hydrocarbons, while the TCA/Y-Zeolite catalyst was active and selective for producing alcohols, with a conversion of 66% and showed 55% selectivity for α-terpineol at 10 min. The reaction taken place in a solid-liquid mode and most of the α-terpineol is extracted out by the organic phase during the course of the reaction. TCA/Y-Zeolite was found as good catalyst for hydration of α-pinene to produce α-terpineol.